Evalution of System Success on CRM Applications - Karahoca, Adem; Baklan Şen, Banu; Karahoca, Dilek (Global Journal onTechnology, 2015)
"The purpose of this study is to observe sales process and measure of the system success on CRM applications which are technologic innovation. In this study, DeLone and McLean [1] model is used in order to measure system success. According to the indicators of this model, system quality, information quality, system use, user satisfaction, individual affect and organizational affect are evaluated. The survey was made for this study. The survey was performed for the CRM users in a private company in Turkey. A study area of the survey was determined, before analyzing. Also, according to the departments, different IT projects were introduced. Application of the survey has been carried out to 100 people. The data obtained from 100 people in total, were analyzed with SPSS Statistical package. As a result of this study, system quality affects system use positively; user satisfaction and system use directly affects organization impact. Firstly, the basic components of information technology have been examined. The purpose of Information Technologies, the benefits and the problems of implementation has been discussed. The concept of CRM which is composed by Information Technologies is described. Moreover, DeLone and McLean Information System Success Model has been discussed and the influence on the system has been explained. This study shows the researches and the users that The DeLone and McLean model in what way and how affect the Information System Success in terms of individual and organizational impact. The thesis addresses the people from information sector, the CRM users, the producers of the CRM systems, consulting service providers and the people work in sales and the marketing field."
Keywords: CRM; DeLone and McLean Model; Information Technology; CRM Application Success